Practical Method of Tahfidz al-Qur'an for Early Childhood - Muthoifin Muthoifin; Ari Kurniawati (Prosiding University Research Colloquium, 2021)
This study focuses on the implementation of the Qur'an tahfidz program for early childhoodusing the Tabarak method at Rutaba Amanah Sragen and the Zahrawain method at theTahfidz Toddler School Zahrawain Surakarta. This study aims to describe how theimplementation of the tahfidzul Qur'an program for early childhood in each of theseinstitutions, describe the supporting and inhibiting factors during the learning process,describe the comparison of the implementation of the two methods for the tahfidzul Qur'anprogram for early childhood. The method used in this study is a comparative descriptivestudy with a qualitative approach. Sources of data obtained from primary data andsecondary data. Data collection techniques are observation, interviews, anddocumentation. The data analysis uses the stages of data reduction, data presentation, andconcluding. The results of research at each institution include curriculum objectives,curriculum materials, targets for memorizing the Qur'an, implementation of methods,evaluation of learning as well as supporting and inhibiting factors for learning. The resultsof the research show that both methods utilize audiovisual media in the learning process,the Tabarak method which comes directly from Egypt has a more dense curriculum targetthan the Zahrawain method which adapts the capabilities of the Indonesian people. Thisis based on the time needed to memorize 30 juz of the Qur'an faster using the Tabarakmethod than the Zahrawain method.